Two Models to Improve Undergraduate Writing Perception and Capabilities in Plant and Soil Sciences (Global Journal of Human-Social Science, 2021)
Integration of professional writing with peer and instructor feedback as a graded component can be a strategy for writing improvement in an applied science undergraduate curriculum. The objective of this study was to assess the benefit of professional writing in first and second-year undergraduate courses in Agronomy and Horticulture with two different models for the writing experience. In the first-year course, students communicated the results of two plant growth experiments in the format of a standard research article. In the second-year course, students wrote a group report as a review of published research or a research-based proposal to address a soil management issue. Students were surveyed to determine their major and learning style evaluated with an 18-question assessment. Students also chose their level of agreement with seven statements about the process and importance of professional scientific writing at the beginning and then at the end of the semester. Survey results showed that confidence in using and creating professional writing increased among students for both courses. Students in the first-year course showed a greater understanding of the value of peer reviewed research.
Keywords: undergraduate; writing perception; writing capabilities; plant science; soil science